A nude mouse model of hypertrophic scar shows morphologic and histologic characteristics of human hypertrophic scar. Issue 1 (5th November 2012) - Momtazi, Moein; Kwan, Peter; Ding, Jie; Anderson, Colin C.; Honardoust, Dariush; Goekjian, Serge; Tredget, Edward E.
Abstract Hypertrophic scar (HSc) is a fibroproliferative disorder that occurs following deep dermal injury. Lack of a relevant animal model is one barrier toward better understanding its pathophysiology. Our objective is to demonstrate that grafting split‐thickness human skin onto nude mice results in survival of engrafted human skin and murine scars that are morphologically, histologically, and immunohistochemically consistent with human HSc. Twenty nude mice were xenografted with split‐thickness human skin. Animals were euthanized at 30, 60, 120, and 180 days postoperatively. Eighteen controls were autografted with full‐thickness nude mouse skin and euthanized at 30 and 60 days postoperatively. Scar biopsies were harvested at each time point. Blinded scar assessment was performed using a modified Manchester Scar Scale. Histologic analysis included hematoxylin and eosin, Masson's trichrome, toluidine blue, and picrosirius red staining. Immunohistochemistry included anti‐human human leukocyte antigen‐ABC, α‐smooth muscle actin, decorin, and biglycan staining. Xenografted mice developed red, shiny, elevated scars similar to human HSc and supported by blinded scar assessment. Autograft controls appeared morphologically and histologically similar to normal skin. Xenografts survived up to 180 days and showed increased thickness, loss of hair follicles, adnexal structures and rete pegs, hypercellularity, whorled collagen fibers parallel to the surface, myofibroblasts, decreased decorin and increased biglycan expression, and increased mast cell density. Grafting split‐thickness human skin onto nude mice results in persistent scars that show morphologic, histologic, and immunohistochemical consistency with human HSc. Therefore, this model provides a promising technique to study HSc formation and to test novel treatment options.